Results from a pragmatic prospective cohort study: Shared decision making improves outcomes for children with asthma. (21st April 2017) - Tapp, Hazel; Shade, Lindsay; Mahabaleshwarkar, Rohan; Taylor, Yhenneko J.; Ludden, Thomas; Dulin, Michael F.
ABSTRACT: Objective : Patient/provider shared decision making (SDM) improves asthma control in a pragmatic clinical trial setting. This study evaluated the impact of an evidence-based SDM toolkit on outcomes for patients with asthma implemented by providers in a real world setting. We hypothesized that these patients with asthma would demonstrate improved outcomes such as reduced emergency department (ED) visits, hospitalizations, and oral steroid use in the 12 months following a SDM visit compared to those who did not receive the intervention. Methods : Patients with asthma were identified within six primary care practices that serve vulnerable populations in Charlotte, NC (746 children; 718 adult patients). Propensity scores were used to match 200 children and 206 adults for analysis. The primary outcome variable was asthma exacerbation defined as an ED visit or hospitalization for asthma or outpatient prescription of an oral steroid. Patients were monitored at 3, 6, and 12 months after the intervention date. The outcome variables of ED visits, hospitalizations, and oral steroids were compared between intervention and matched control patients. Results : The proportion of pediatric patients with one or more exacerbations was significantly lower in the SDM intervention group compared to controls during 12 months after exposure to the intervention (33% vs. 47%, p = 0.023). For adults, there was not a strong association between use of the SDM intervention and outcomes improvement. Conclusions : The evidence-based SDM intervention implemented in this study was associated with improved asthma outcomes for pediatric patients but not adult patients in a real world clinical setting.